Effect of a Phytogenic Feed Additive in Preventing Calves' Diarrhea - Turini, Luca; Mantino, Alberto; Tozzi, Beatrice; Bonelli, Francesca; Silvi, Alina; Mele, Marcello; Sgorbini, Micaela; Meucci, Valentina; Minieri, Sara (Frontiers in Veterinary Science, 2022)
The aims of the present study were to evaluate the preventive and the therapeutic effect of Stodi® as phytogenic feed additive rich in phenolic substances on the calf diarrhea, during the first 21 days of life. A total of 40 calves were included and randomly divided into Group C (control group) and Group T (treated group) with placebo or treatment administration started from the third day of life (T0). Calves belonged to group C received 2 L of warm water, while the calves assigned to group T received 2L of warm water plus 30 g of Stodi®. Solutions administration was maintained until day 21 (T21) that was the end of the experimental period. Calves were weighed at T0 and T21 to assess the average daily gain (ADG). Physical examination and fecal score evaluation were performed daily. The duration of a diarrheic episode, the age of the first diarrhea outbreak (TDE) and the frequency of diarrheic episodes were recorded. Complete blood count, methemoglobin and liver enzymes were evaluated at T0 and at T21 in all the calves by spectrophotometer and clinical chemistry analysis, respectively. Data were analyzed using a mixed model. A Chi-square and a Mann-Whitney test were also performed. No difference was found for ADG between the groups. The difference of mean age at TDE was not statistically significant between C and T group. The number of calves with diarrhea in the C group tended to be higher than that of T group (p = 0.13). Calves in group C spent more days with clinical sign of diarrhea compared to group T (p = 0.016). Complete blood count, methemoglobin and liver enzymes were within the reference ranges. The feed additive Stodi® seemed to be effective in shortening neonatal diarrhea episodes in calves thanks to the administration of 30 g per day of product. The fixed dosage of Stodi® used in our study did not show a preventive effect to reduce the incidence of calf diarrhea.